E-075 National survey on flow diverting stents for intracranial aneurysms in the United States. (23rd July 2022) - Salem, M; Elfil, M; Aboutaleb, P; Dmytriw, A; Thomas, A; Hassan, A; Mascitelli, J; Kan, P; Jankowitz, B; Burkhardt, J
Abstract : Introduction: The Pipeline Embolization Device (PED) has been the only FDA-approved flow-diverting device (FDD) in the US market for nearly a decade. There has been more FDD choices in the US following recent FDA approval of the Flow Redirection Endoluminal Device (FRED) and Surpass into the American market. Methods: A 34-questions electronic survey was distributed to members of the neurointerventional community in the United States from different training backgrounds (Neurosurgery, Neurology, and Neuroradiology) through the American Association of Neurological Surgeons (AANS), Society of Vascular and Interventional Neurology (SVIN), and Society of NeuroInterventional Surgery (SNIS) mailing lists and through social media links. The survey focused on the technical aspects of device selection and personal preferences/experiences regarding their approach to the different devices in aneurysms treatment. Results: Survey responses were collected from 120 neurointerventionalists across the US, with operators from Neurosurgery background constituting the majority of respondents (47.5%) with 85% of them being dual-trained. The largest age block was early-to mid-career operators (70.8% aged 36–50 years). Most participating interventionalists (78.8%) treated a range of 25–100 aneurysms/year with FDDs, with 10.2% treating >100/year. Around half of respondents (49.2%) stated that they have all the FDA-approved FDDs available in their centers (80.8% academic practice). The femoral access was utilized by the majority of respondents (67.7%), without significant difference of FDD-device on access-type (89.2%). PED was the most commonly utilized device (70.9%), with 66.7% of respondents reporting using different FDD based on case specifics including anatomy and location. PED was endorsed as the most common choice for giant aneurysms and in ruptured cases (particularly PED Shield), while FRED Jr was preferred for distal aneurysms with small parent vessel diameters, and Surpass was the FDD of choice for aneurysms with large parent vessels. When comparing devices preferences based on training backgrounds, more operators from neurosurgical background endorsed PED as their most commonly utilized device (81.5% vs 66.7%; p=0.06), while more interventional neuroradiologists/neurologists reported Surpass (27.3% vs 13%; p=0.05) and FRED (30.3% vs 13%; p=0.024) as their most commonly utilized devices. Conclusion: The results of this survey will help to identify common patterns in FDD choices among treating neurointerventionalists in the US market, along with their integration patterns of the newly introduced devices. As the experience continues to grow with these devices, operators' techniques will likely continue to evolve to adapt to the continuous expansions of the neurointerventional armamentarium. Disclosures: M. Salem: None. M. Elfil: None. P. Aboutaleb: None. A. Dmytriw: None. A. Thomas: None. A. Hassan: None. J. Mascitelli: None. P. Kan: None. B. Jankowitz: None. J. Burkhardt: None.